Radiation and temperature effects on electrical properties of poly (vinyl alcohol) - sodium salicylate polymer electrolytes - Ahad, Noorhanim (2011)
The solid composite polymer electrolytes (SCPEs) are materials that have attracted great attention for their application in the development of solid-state ionic devices. The physical and chemical properties of SCPEs can be modified by treatment with ionizing radiation. One major problem relating to these solid electrolytes is that they have tendency to crystallize at room temperature resulting in a reduction of the ionic conductivity. In this study, radiation processing technique was chosen to increase the ionic conductivity at room temperature. The SCPEs consists of poly (vinyl alcohol)(PVA) and sodium salicylate (SS) as ionic blend were prepared by solvent-casting technique at different SS concentrations (0, 10, 20, 30, 40, 50 wt %) and the film samples were irradiated with gamma radiation at different doses (0, 10, 20, 40 and 50 kGy) at room conditions. The irradiated and unirradiated film samples of different compositions were each placed between two parallel-plate metal electrode and the electrical conductivity and dielectric properties were measured using an impedance analyzer at frequencies ranging from 20 Hz to 1 MHz. The unirradiated samples were also treated thermally and the conductivity and dielectric properties were measured at different temperatures of 303 to 353 K. The X-Ray diffraction (XRD)analyses were performed to characterize the change of molecular structure of the SCPEs with radiation dose and compositions of the ionic blend. For the unirradiated samples, the complexation and interaction in SCPEs were measured by using Fourier Transform Infrared (FTIR) Spectroscopy and the thermal stability of the SCPEs was investigated by thermogravimetric analysis using a Perkin Elmer TGA Instrument. The results show that the conductivity and dielectric properties of PVA-SS SCPEs depend on composition of the ionic blends, temperature and radiation dose. The conductivity and dielectric value increase with increasing SS composition due to increase of the number of charge carriers, mainly ions introduced in the blends. The sample of 50 wt. % SS irradiated with dose of 50 kGy exhibits the highest conductivity at room temperature is ~10-7 to 10-6 S/cm. The dc conductivity follows the equation 0 ( 0 ) exp D/ D dc σ =σ which is characterized by the dose sensitivity, D0. It was found that the lowest dose sensitivity is the characteristic of PVA-SS polymer electrolyte of the highest conductivity(50 wt.%, D0 = 0.017). The dc conductivity is associated with sodium and hydrogen ions and free ions that mainly induced from γ- ray interaction. The temperature effects on the conductivity of SCPEs follow Arrhenius equation,      =kT EA dc exp 0 σ σ which characterized by the activation energy,EA and for 50 wt. % SS sample, the highest conductivity is at 353 K (~10-7 to 10-6 S/cm). The highest activation energy is the characteristic of pure PVA polymer (EA =0.729 eV). The effect of temperature on conductivity is due to increase of ionic mobility of charge carriers by a factor proportional to kT. From the XRD analysis,the results show that the degree of crystallinity of the PVA decreases with the increase of SS composition. As the compositions increase to 30, 40 and 50 wt.% SS,the XRD patterns become crystalline because several peaks have been emerged but the intensity of these peak turns decreases when the dose increases. From the results, we have demonstrated that the radiation can be used to increase the conductivity of SCPEs for the development of solid-state ionic devices.